A bioética ambiental como instrumento para o aperfeiçoamento do desenvolvimento sustentável - Santos, Emmanuely Poncell dos (2014)
The overall objective of this research is to analyze the environmental ethics useful tool for the improvement of sustainable development, proposed by Ignacy Sachs. Therefore, the specific objectives are: a) to understand the sustainable development model proposed by Ignacy Sachs; b) to think of the bioethics related to environmental issues, based on José Roque Junges, (Bio) ética ambiental; c) to analyze the environmental ethics as reflection of ethical bases tool for advancing sustainable development, proposed by Sachs, based in José Roberto Goldim, Bioética: origens e complexidade, Marie-Helène Parizeau and Paul Ricoeur (from his contributions to the Dicionário de Ética e Filosofia Moral, by Monique Canto-Sperber). The search problem is: what are the contributions of environmental bioethics for the improvement of the sustainable development model proposed by Ignacy Sachs. Thus, the hypothesis to be tested is that Bioethics contributes to the advancement of Environmental sustainable development, insofar as it is able to determine an ethical reflection and interdisciplinary practice support a debate driven by ecological dimensions, environmental, social, economic, political, cultural and territorial. This is a fundamental nature or theoretical, bibliographical, exploratory and qualitative approach, which uses the hypothetical-deductive approach method, the method of historical procedure and the bibliographic data collection procedure. The technique of the research is the analysis of content. The relevance of this research is in contributing to the improvement of the sustainable development model proposed by Ignacy Sachs, to the extent that extends the discussion about the ethical bases mentioned by the author. The contribution is also reflected in an instrument able to establish levels of reflections on the ethical bases necessary to the construction of the environmental debate, to the confronting the dilemma between environmental protection and economic development, advancing in the knowledge of the areas of bioethics and Environmental Sciences and establishing future research grants.